A critical analysis of CSR initiatives of the top 10 fortune 500 companies before and during COVID-19 - Malla, Ashma; Levermore, Roger; Zimmermann, Willi; Vatcharapol Sukhotu; Asian Institute of Technology Fellowship (2021)
While CSR was one of the major focal points for most companies, the COVID-19 pandemic brought about a significant upheaval in their priorities. In this context, the study aims to identify and understand the CSR initiatives of the top ten Fortune 500 companies during COVID-19 and compare it with the pre-COVID-19 period. An empirical case study analysis was carried out to gain in-depth insights regarding those initiatives. The research used a variety of data sources including press releases, annual reports, and news articles, to base its findings on the current situation. The information was accessed from the respective company{u2019}s websites. The result indicated that all these companies were particularly focused on the philanthropic and economic dimensions of CSR during the pandemic such as making donations to vulnerable communities and taking precautionary operational measures to safeguard employees and consumers. However, while comparing those initiatives with pre-COVID CSR initiatives, it could be seen that those initiatives were implemented without keeping in mind the environmental dimension. Those initiatives were short-term and lacked overall sustainability.
A project submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Project (M.B.A.) - Asian Institute of Technology, 2021
Keywords: Corporate social responsibility series; Social responsibility of business; COVID-19 Pandemic, 2020-